2016
DOI: 10.5194/gmd-9-3177-2016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced representation of soil NO emissions in the Community Multiscale Air Quality (CMAQ) model version 5.0.2

Abstract: Abstract. Modeling of soil nitric oxide (NO) emissions is highly uncertain and may misrepresent its spatial and temporal distribution. This study builds upon a recently introduced parameterization to improve the timing and spatial distribution of soil NO emission estimates in the Community Multiscale Air Quality (CMAQ) model. The parameterization considers soil parameters, meteorology, land use, and mineral nitrogen (N) availability to estimate NO emissions. We incorporate daily year-specific fertilizer data f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…Code availability. The modified and new source code, inputs, and sample outputs along with the user manual giving details on implementing the new mechanistic module in-line with CMAQ version 5.1, as used in this work, are available on the Oak Ridge National Laboratory Distributed Active Archive Center for Bio-geochemical Dynamics (Rasool et al, 2018; https://doi.org/10.3334/ORNLDAAC/1661). Source codes for CMAQ version 5.1 and FEST-C version 1.2 are both open source and available with applicable free registration at http://www.…”
Section: Discussionmentioning
confidence: 99%
“…Code availability. The modified and new source code, inputs, and sample outputs along with the user manual giving details on implementing the new mechanistic module in-line with CMAQ version 5.1, as used in this work, are available on the Oak Ridge National Laboratory Distributed Active Archive Center for Bio-geochemical Dynamics (Rasool et al, 2018; https://doi.org/10.3334/ORNLDAAC/1661). Source codes for CMAQ version 5.1 and FEST-C version 1.2 are both open source and available with applicable free registration at http://www.…”
Section: Discussionmentioning
confidence: 99%
“…Biogenic and lightning emissions are calculated online; biogenic emissions are calculated using BEIS v3.14. Soil NO x emissions are not included here because the CMAQ soil NO x parameterization was implemented in a newer version of the model (Rasool et al, 2016). This model simulation utilizes CB05 gas-phase chemistry.…”
Section: Cmaq Model Simulationmentioning
confidence: 99%
“…This simulation did not include NO x emissions from soils. Rasool et al (2016) has shown soil NO x emissions to be particularly important in the central US, with a lesser role in the eastern US. Excluding these emissions may have resulted in less NO x being transported from upwind regions.…”
Section: Omi_cmaq Vs Cmaqmentioning
confidence: 99%
See 1 more Smart Citation
“…and Europe (Huijnen et al, 2010;Curier et al, 2014). It has also been used to produce and validate NOx emission estimates from sectors such as soil (Hudman et al, 2010;Vinken et al, 2014a;Rasool et al, 2016), lightning (Allen et al, 2012;Liaskos et al, 2015;Pickering et al, 2016;Nault et al, 2017), power plants (de Foy et al, 2015), aircraft (Pujadas et al, 2011), marine vessels (Vinken et al, 2014b;, and urban centers (Lu et al, 2015;Canty et al, 2015;Souri et al, 2016).…”
mentioning
confidence: 99%